Cloud data center network architectures and technologies - Zhang, Lei (Engineering teacher); Chen, Le (Writer on computer networking) (Boca Raton : CRC Press, 2021)
"This book has been written with the support of Huawei's large accumulation of technical knowledge and experience in the data center network (DCN) field, as well as its understanding of customer service requirements. This book describes in detail the architecture design, technical implementation, planning and design, and deployment suggestions for cloud DCNs based on the service challenges faced by cloud DCNs. This book starts by describing the overall architecture and technical evolution of DCNs, with the aim of helping readers understand the development of DCNs. It then proceeds to explain the design and implementation of cloud DCNs, including the service model of a single data center (DC), construction of physical and logical networks of DCs, construction of multiple DCNs, and security solutions of DCs. Next, this book dives deep into practices of cloud DCN deployment based on real-world cases to help readers better understand how to build cloud DCNs. Finally, this book introduces DCN openness and some of the hottest forward-looking technologies. In summary, you can use this book as a reference to help you to build secure, reliable, efficient, and open cloud DCNs. It is intended for technical professionals of enterprises, research institutes, information departments, and DCs, as well as teachers and students of computer network-related majors in colleges and universities"--
OCLC-licensed vendor bibliographic record.
Keywords: Cloud computing; Computer network architectures; COMPUTERS / Internet / General; MATHEMATICS / General